Análisis del discurso del presidente Daniel Noboa en la plataforma Instagram en el primer año de gestión - Ramírez Parrales, Lisbeth Xiomara (2025)
Critical Discourse Analysis (CDA) is a fundamental tool for studying political communication, as it examines language within the context of social dynamics. This approach allows us to identify the mechanisms that shape political discourse and how they influence voters' perceptions. This article presents a documentary research study that employs a mixed-methods approach to analyze the elements that make up the discursive strategies used on Instagram by Ecuadorian President Daniel Noboa. The research tools include a documentary review of social media posts, content analysis, discourse analysis, and interviews that gather insights from experts in political and digital communication. The study describes the elements that constitute the president's Instagram discourse during his first year in office. The use of these tools reveals Noboa's focus on building his public image as both a young and approachable politician. His content on this platform highlights his administration's fight against insecurity, a topic of significant concern to Ecuadorians. Additionally, he uses symbolically charged imagery that often conveys patriotism or the endorsement of traditional values.